2015
DOI: 10.1002/jocc.12017
|View full text |Cite
|
Sign up to set email alerts
|

Brief Therapy at a University Counseling Center: Working Alliance, Readiness to Change, and Symptom Severity

Abstract: The authors investigated whether students receiving short-term individual counseling at a university counseling center showed progress as evidenced by perceived client and counselor outcomes and the roles that client readiness to change and working alliance played in this setting. The results indicated that the counselor reports, not the client reports, reflected statistically significant change in client symptoms. Changes in symptom severity were not associated with working alliance and readiness to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
5
13
0
Order By: Relevance
“…There were only 15 participants in the complete-data sample. Although such client loss is consistent with prior research (e.g., Draper et al, 2002;Ghetie, 2007;Lucas, 2012;Mahon et al, 2015), it was none-the-less discouraging. The four-year data collection has stopped due to several reasons, including the UCC moving to a new location and some key staff turnover, but general lack of client response was the primary issue.…”
Section: Study Limitationssupporting
confidence: 84%
See 3 more Smart Citations
“…There were only 15 participants in the complete-data sample. Although such client loss is consistent with prior research (e.g., Draper et al, 2002;Ghetie, 2007;Lucas, 2012;Mahon et al, 2015), it was none-the-less discouraging. The four-year data collection has stopped due to several reasons, including the UCC moving to a new location and some key staff turnover, but general lack of client response was the primary issue.…”
Section: Study Limitationssupporting
confidence: 84%
“…Such research supports having the resources available in a UCC to avoid "time limited" treatment (Ghetie, 2007). Many college students successfully engage in short-term treatment (Mahon et al, 2015). However, knowing that additional sessions can lead to further benefits in terms of reduced mental health concerns and increased counseling help belief should help to justify a UCC having the resources in place, such as adequate staffing, to avoid having a fixed number or cap of sessions with non-urgent college students (AUCCD, 2016;CCMH, 2017;Lucas, 2012).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In another review, Ghetie (2007, p. 51) noted a median (midpoint of a frequency distribution) of 4-5 counseling sessions and a mode (most frequent number) between 1 and 2 sessions. Mahon et al (2015) found that 37/124 (30%) of undergraduate clients completed a minimum of three counseling sessions, with the remaining 87 either never returning for a second session or dropping out after two sessions. While it can be very challenging to build a longer-term sample of undergraduates receiving counseling services, prior research suggests that even a short-term intervention can increase important undergraduate outcomes.…”
Section: Brief Nature Of College Counselingmentioning
confidence: 99%